Expropriation of minority shareholders' rights: Evidence from Malaysia - Mustafa, Nurul Huda; Abdul Latif, Rohaida; Taliyang, Siti Mariana (Centre for Promoting Ideas, 2011)
The objectives of this study are to investigate the factors and the extent level of expropriation of minority shareholders’ rights in context of Malaysia.Analysis of sixty companies listed from two industries in Bursa Malaysia was selected.Descriptive analysis and ordinary least squares (OLS) regression model are performed in this study The variables tested are ownership concentration, firm size, board independence, profitability, level of leverage and firm growth.From these variables, only three variables can be concluded as factors influencing the expropriation of minority shareholders' rights in Malaysia. The number of independent outside directors increases the potential for expropriation of minority shareholders' rights.However, this relationship became opposite when the directors have a different characteristic among boards that affect their independence level.Profitability and growth are highly correlated.When the model is estimated using either one of them, the result is significantly negative, which means that profitable or growing firms have less incentives to engage in related party transactions.